KARAKTERISASI BAHAN FEROELEKTRIK BARIUM STRONTIUM TITANAT (Ba0,7 Sr0,3TiO3) MENGGUNAKAN MIKROSKOP IMBASAN ELEKTRON (SEM) - Rizki, Befriana Ayu; Dewi, Rahmi; ', Sugianto (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Ferroelectric of Ba0,7Sr0,3TiO3 has been made from BaCO3 (Barium Carbonat), SrCO3(Strontium Carbonat), and TiO2 (Titanat Oksida) with variation of calcination temperatures of 600oC, 700oC, and 800oC. Ferroelectric product of Ba0,7Sr0,3TiO3 was characterized by Scanning Electron Microscopy (SEM). Sizes of ferroelectric particle increased with sintering temperatures, as follow 1,67µm, 2,27µm, and 2,38µm for samples with high temperature of 600oC, 700oC and 800oC. Respectively then the density of particle decreased with temperature i.e 5,03x10-4 %, 4,40x10-4 %, and 1,52x10-4 %. The average value of resistance increased with calcination temperature and sintering temperature of 400oC, 600oC, 700oC and 800°C i.e 6,716x108Ω, 6,740x108 Ω, 6,754x10 8 Ω and 6,768x108 Ω, as well as the value of the average resistivity increased with rise in calcination temperature and sintering temperature as follow 193,122x108 Ωm, 194,884x108 Ωm, 196,784x108 Ωm, and 198,882x108Ωm. These were due to the effect of temperature on the arrangement of the material atoms. It was concluded then the resistivity of a material does not depend on its geometric shape but depend on the temperature of the material.